2020
DOI: 10.22541/au.159986464.41142982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subcutaneous Allergen Immunotherapy in Children: Real Life Compliance and Effect of COVID-19 Pandemic on Compliance

Abstract: Background: Allergen immunotherapy(AIT) is an effective treatment for allergic rhinitis, asthma and venom allergy. Compliance is essential for AIT to obtain maximal benefit as it is a long term treatment. Objective: We aimed to evaluate the real life compliance of children with subcutaneous immunotherapy(SCIT) and tried to document the factors associated. Additionally how COVID-19 pandemic effected the compliance of the patients and the reasons of drop-outs were also evaluated. Method: Patients diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…143 As the success of SCIT is thought to depend on regular injections; a 30% SCIT dropout has been noticed among children and 23.81% among adults due to the fear of contracting COVID-19. 144,145 The implementation of novel strategies to effectively manage AR patients receiving SCIT is thus critical as numerous patients delay the treatment during the COVID-19 pandemic. 146 Recently, Xi et al 147 have proposed a novel dose adjustment SCIT schedule beginning with a 10,000 SQ dose (vial 4), and demonstrated that this was equally effective and safe to the conventional schedule beginning with a 10 SQ dose (vial 1) for delayed SCIT of more than 16 weeks.…”
Section: Ar Patient Manag Ement During the Covid -19 Pandemi Cmentioning
confidence: 99%
See 1 more Smart Citation
“…143 As the success of SCIT is thought to depend on regular injections; a 30% SCIT dropout has been noticed among children and 23.81% among adults due to the fear of contracting COVID-19. 144,145 The implementation of novel strategies to effectively manage AR patients receiving SCIT is thus critical as numerous patients delay the treatment during the COVID-19 pandemic. 146 Recently, Xi et al 147 have proposed a novel dose adjustment SCIT schedule beginning with a 10,000 SQ dose (vial 4), and demonstrated that this was equally effective and safe to the conventional schedule beginning with a 10 SQ dose (vial 1) for delayed SCIT of more than 16 weeks.…”
Section: Ar Patient Manag Ement During the Covid -19 Pandemi Cmentioning
confidence: 99%
“…In the case of AR patients without a COVID‐19 infection, the guideline‐based pharmacological treatment should be continued as ICS therapy and the usage of conventional drugs such as antihistamines or β2 adrenoceptor agonists are irrelevant to the COVID‐19 infection 143 . As the success of SCIT is thought to depend on regular injections; a 30% SCIT dropout has been noticed among children and 23.81% among adults due to the fear of contracting COVID‐19 144,145 . The implementation of novel strategies to effectively manage AR patients receiving SCIT is thus critical as numerous patients delay the treatment during the COVID‐19 pandemic 146 .…”
Section: Ar Patient Management During the Covid‐19 Pandemicmentioning
confidence: 99%
“…Some real‐life and modeling studies at the time of pandemic demonstrated that home immunotherapy self‐administration can be a safe and cost‐effective option if patients are carefully preselected 113 . On average, one in three patients managed with subcutaneous immunotherapy (SCIT) discontinued the treatment during the COVID‐19 pandemic 92,114 with being infected with COVID‐19 and thinking that the AIT practice stopped because of pandemic were among the most common reasons for cessation. An international survey of physicians carried out by EAACI reported no concerns regarding reduced tolerability of AIT under real‐life circumstances 115 .…”
Section: Management Of Allergic Diseases During Pandemicmentioning
confidence: 99%
“…Although there is evidence that the COVID-19 pandemic could have interrupted or altered the administration of AIT, there is limited data on the extent of these disruptions and their potential clinical effects. [10][11][12] Italy was the first European country to experience the spread of the COVID-19 virus in February 2020, which greatly impacted the healthcare system of the country, 13 and Italian physicians pioneered the organization of an allergy clinic during the breakout. 14 However, the experience of allergists with respect to ongoing or new AIT prescriptions is unknown.…”
Section: Introductionmentioning
confidence: 99%